EVALUASI KINERJA BUNDARAN BUNDA SRI MERSING MENGGUNAKAN MKJI 1997 DAN SOFTWARE PTV VISSIM - Nur Ilman; Muhammad Idham (Racic : Rab Construction Research, 2023)
The Bunda Sri Mersing Signal Roundabout is the roundabout which is the initial entrance to the City of Dumai and has the problem of increasing high traffic, and it is necessary to evaluate road performance so that the degree of saturation and impact can be identified. The research is based on the 1997 Indonesian Road Capacity Manual method and the model uses the PTV Vissim Application, data obtained from field survey results is needed. Based on the results of the analysis, it is known that the value of junior high school traffic flow/hour on the highest day is on Wednesday for weekdays, and Saturday for holidays, so that traffic performance is obtained in the existing conditions, 5 years and 10 years. from data processing using MKJI 1997 it is known that the Degree of Saturation and Level Of Service (LOS) on Jalan Bukit Datuk in the Existing conditions and conditions of 5 years are safe, and in conditions of 10 years DJ and Level Of Service (LOS) have problems with the degree of saturation of 0,85.